Research on Quantization Error Influence of Millimeter-Wave Phased Array Antenna - Haigen Yang; Linqun Zhu; Zhun Xia; Yanqing Chen; Luohao Dai; Ruotian Xu; YuanHao Chen; Luyang Li; GuiYing Sun; Hongyang Yu; Wenting Xu (International Journal of Antennas and Propagation)
The millimeter-wave phased array antenna is a higher integration system that is composed of different subarray modules, and in actual engineering, the existing amplitude, phase errors, and structural errors will change the performance of the array antenna. This paper studies the influence of the random amplitude and phase errors of the antenna array in the actual assembly process and the actual position errors between the subarrays on the electrical performance of the antenna. Based on the planar rectangular antenna array-electromagnetic coupling model, we propose a method of verifying the effect of random errors on the phased array antenna. The simulation result shows that the method could obtain the critical value of the error generated by the antenna subarray during processing and assembly. To reduce the error factor, it is necessary to ensure that the random phase and amplitude error should not exceed 10°,0.5 dB. The error in the X-direction during assembly should be ≤0.05λ, and the error in the Y-direction should be ≤0.1λ. When symmetrical deformation occurs, the maximum deformation should be less than 0.05λ.